(untitled) (Research, Society and Development, 2021)
Physical exercise programs help to mitigate the harmful effects of aging, such as processes related to insulin resistance and type 2 diabetes mellitus in the elderly. Based on this assumption, the present study aims to identify the effects of the HIIT program on the metabolic profile of elderly people with type 2 diabetes. The study is a bibliographic research with a qualitative approach. It was observed that HIIT acts directly in the lipotoxicity process, reducing levels of free circulating fatty acids, as well as, in reducing the expression of pro-inflammatory adipokines. It is concluded that HIIT is a valuable tool for the control / attenuation of insulin resistance in elderly type 2 diabetics.